Pengaruh Sistem Insentif Terhadap Efektivitas Kinerja Dinas Pendapatan Daerah Kota Palangka Raya = Influence of Incentive System to Performance Effectiveness of The Local Revenue Collection Departement of Palangka Raya C - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
This study aims to get empirical evidence about influence of incentive system to performance effectiveness of The Local Revenue Collection Departement of Palangka Raya City. Sample used is five type of Local Original Revenue (PAD) of Palangka Raya City like Hotel and Restaurant tax, Market Retribution, Rent Shop and Building Retribution, Hygiene Service Retribution and Park Retribution. This research uses time series data of incentive, realization and budget from each type of the PAD, 1999-2003. The data collection uses questiona re which addressed to Head Of The Local Revenue Collection Departement of Palangka Raya. Data analysis uses simple regression. The result of study indicates that incentive system does not have an effect on the performance effectiveness On The Local Revenue Collection Departement of Palangka Raya (F=1,862